ДИАГНОСТИКА И ОПРЕДЕЛЕНИЕ НАПРАВЛЕНИЙ ПРИМЕНЕНИЯ АРТ-ПЕДАГОГИЧЕСКИХ ТЕХНОЛОГИЙ В ЭСТЕТИЧЕСКОМ ВОСПИТАНИИ МЛАДШИХ ШКОЛЬНИКОВ - Куттибекова, Г.Т. (SCIENCE and SOCIETY, 2020)
The article illustrates the idea of complex approach to the diagnostics and applying of art pedagogy as an innovational technology to improve the process of aesthetic upbringing during art and music classes in primary schools.
Keywords: pupils; complex; aesthetic upbringing; aesthetic mannerliness; art pedagogy; diagnostics; components; criteria; trends